Flipped Classroom Model Combined with Problem-Based Learning: Increase Thinking Ability - Rahayu, Mitra Nata; Mariono, Andi; D., Syaiputra W. (Akademika, 2024)
The growing complexity of real-world problems has heightened the need for critical thinking skills in education, particularly in fields like statistical education. This study examines the integration of the Flipped Classroom (FC) model with Problem-Based Learning (PBL) to foster critical thinking among university students. Conducted at Bhineka University, the research involved 60 students divided into experimental (FC+PBL) and control (PBL-only) groups. A mixed-methods approach was employed, combining pre-tests, post-tests, classroom observations, and reflective journals to collect quantitative and qualitative data. The experimental group participated in pre-class activities such as video lectures and quizzes, with in-class sessions focusing on collaborative problem-solving guided by PBL principles. Analysis of Variance (ANOVA) revealed a significant improvement in critical thinking skills in the FC+PBL group compared to the PBL-only group (p < 0.001). Qualitative findings highlighted increased engagement, collaboration, and deeper inquiry among the experimental group. These results underscore the potential of integrating FC and PBL to create dynamic, student-centered learning environments that enhance critical thinking and prepare students to tackle complex challenges effectively